A Comparative In Vitro Analysis of Attachment and Enhanced Structural Features for Molar Distalization in Clear Aligner Therapy - Youn-Kyung Choi; Min-Jeong Jee; Sung-Hun Kim; Seong-Sik Kim; Soo-Byung Park; Yong-Il Kim (Applied Sciences)
This study evaluated the effects of different clear aligner (CA) designs on forces and moments during maxillary second molar distalization. Four designs were tested: attachment only (group 1), neither attachment nor enhanced structure (group 2), a combination of attachment and enhanced structure (group 3), and enhanced structure only (group 4). CAs were fabricated from thermoformed polyethylene terephthalate glycol with 30 CAs per group. Forces and moments were measured using a multi-axis transducer as the molars were distally displaced by 0.25 mm. All groups experienced buccodistal and intrusive forces. Group 3 showed the highest distalizing force (Fy = 2.51 ± 0.37 N) and intrusive force (Fz = −2.04 ± 0.48 N) and also the largest rotational moment (Mz = 3.89 ± 0.71 Nmm). Groups 3 and 4 (with enhanced structures) demonstrated significant intrusive forces (p < 0.05). Most groups exhibited mesiodistal angulation, lingual inclination, and distal rotational moments. Group 2 had the lowest moment-to-force ratio (Mx/Fy = 3.27 ± 0.44 mm), indicating inefficient bodily movement. Group 3 demonstrated significantly greater moments across all axes compared to other groups. The results indicate that designs incorporating enhanced structures with attachments increase CA stiffness and applied forces/moments, enhancing distalization efficiency while minimizing vertical side effects. This suggests that, clinically, reinforced CAs can serve as a simple yet effective modification to existing protocols in Class II orthodontic cases, enabling more efficient molar distalization without requiring complete appliance redesign or additional fabrication and allowing easy adaptation to individual treatment needs.